(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Mhd Laminar Boundary Flow With Heat And Mass Transfer An Electrically Leading Mhd Williamson And Casson Nano Fluid Over A Penetrable Extending Sheet Installed In A Permeable Medium Has Been Considered In The Impacts Of Attractive Field, Thermal Radiation, And Compound Response. The Administering Halfway Differential Conditions Alongside The Boundary Conditions Were Diminished To Dimensionless Structures By Utilizing Reasonable Closeness Change. The Subsequent Arrangement Of Common Differential Conditions With The Relating Boundary Conditions Was Illuminated Through Runge-Kutta Fehlberg Strategy Alongside Shooting Method. The Consequences Of The Investigation Show That Velocity, Temperature, And Concentration Boundary Layer Thicknesses By And Large Diminishing As We Move Away From The Outside Of The Extending Sheet And The Williamson And Casson Parameter Was Found To Impede The Velocity Profiles. The Physical Parameters Like Skin Friction, Nusselt Number And Sherwood Number Are Discussed In Detail.